Síntomas premenstruales y trastorno disfórico premenstrual en las estudiantes del Área Agropecuaria y de Recursos Naturales Renovables de la Universidad Nacional de Loja, periodo abril - septiembre 2016. - Herrera Samaniego, Dalton Fabián (2017)
One of the topics of interest in women's health includes premenstrual disease, which evolves in its study due to the impact that implies and the interference that produces in the habitual performance, the present study aims to determine the premenstrual symptoms (SM) and Premenstrual Dysphoric Disorder (PMDD) in students of the Agricultural and Natural Renewable Resources Department of the National University of Loja, from April to September 2016. The sample consisted of 209 students and a transversal analytical design was used. The technique that is applied for collecting information for the survey. The results reflect that, the frequent premenstrual symptoms were: Tension, irritability and / or mood changes 81.33%; followed by abdominal distension of 64.59%; Breast hypersensitivity 58.85%; Changes in appetite 58.37%. In addition, it was identified that it meets the criteria for the diagnosis of dysphoric disorder in a 7.18% and does not meet in 92.82%. Likewise, it was determined that of the 15 students who met the exclusion criteria for Premenstrual Dysphoric Disorder in a large part presented psychic symptoms such as: tension, irritability and / or changes in mood (easy crying) with 88, 66%; and fatigue with 73, 33%, and to a lesser extent presented somatic symptoms. Keywords: Prementruales Symptoms, Dysphoric Disorder